Production of concrete pavements using mixed cements - Jan Klobása; Rudolf Hela (Acta Polytechnica CTU Proceedings, 2024)
Currently, great importance is attached to the reduction of emissions in industrial production, especially in the production of cement, when it is indicated that during production 1 ton of cement produces approximately 0.6 ton of CO2. Reducing emissions is possible thanks to secondary raw materials, which are produced in large quantities in the Czech Republic volumes for which a suitable use is sought. Some secondary raw materials are suitable for use in concrete mixes, which are used to improve the rheology of the fresh concrete mixture as well as the properties hardened concrete. Currently, there is an effort to eliminate the production of cement, to which its partial replacement by admixtures could also contribute. Therefore it is necessary determine the optimal admixture that could be used to replace part of the cement in concrete mix. A large consumer of concrete mixes are transport structures, where it is possible for some of the cement used to be replaced by an admixture.